2004
DOI: 10.1002/hep.20425
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effects of a tissue inhibitor of metalloproteinase-1 antibody on established liver fibrosis in rats

Abstract: F ibrosis is associated with many liver diseases, including hepatitis C virus infection, iron deposition, alcohol consumption, and nonalcoholic fatty liver disease. Hepatic fibrosis results from a net increased synthesis and decreased degradation of extracellular matrix (ECM) proteins. Type I collagen is the most prevalent ECM protein deposited, 1 with activated hepatic stellate cells (HSCs) serving as the primary source. Following a fibrogenic stimulus, HSCs activate from their normal quiescent state, whereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(124 citation statements)
references
References 50 publications
6
116
0
2
Order By: Relevance
“…Compared with the results with Sirius Red staining, the decrease in hydroxyproline content was less impressive. The same phenomenon has been reported in previous studies 17,38,39 and may be a result of the hydroxyproline assay detecting not only intact collagen accumulation but also degraded collagen, unlike Sirius Red, which detected only intact collagen.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with the results with Sirius Red staining, the decrease in hydroxyproline content was less impressive. The same phenomenon has been reported in previous studies 17,38,39 and may be a result of the hydroxyproline assay detecting not only intact collagen accumulation but also degraded collagen, unlike Sirius Red, which detected only intact collagen.…”
Section: Discussionsupporting
confidence: 88%
“…In other reports, TIMP-1 levels have been included in non-invasive algorithms to classify the extent of fibrosis (36,37). In support of such a role, animal models have shown that TIMP-1 overexpression promotes liver fibrosis (12) and retards fibrosis resolution (13), and the administration of TIMP-1 blocking antibodies attenuates fibrosis (38). In addition, during the process of fibrosis resolution, reduced TIMP-1 levels result in increased MMP activity and matrix degradation (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…TIMP-1 protects activated HSCs from apoptosis, 46 and blocking TIMP-1 with specific monoclonal antibody reverses CCl 4 -induced hepatic fibrosis. 47 The key to translating the important discovery of the activated-HSC-apoptosis model of fibrosis recovery into a clinical entity of therapeutic value in diseases such as ALD is to design strategies that selectively kill activated HSCs without affecting macrophages and hepatocytes that are critical for recovery and regeneration. For example, gliotoxin is capable of inducing apoptosis not only of HSCs but also of hepatocytes at higher concentrations, 48 thus limiting its clinical usefulness.…”
Section: B1 Apoptosis Of Activated Hscsmentioning
confidence: 99%